2022
DOI: 10.1093/cercor/bhac173
|View full text |Cite
|
Sign up to set email alerts
|

Sulcal depth in prefrontal cortex: a novel predictor of working memory performance

Abstract: The neuroanatomical changes that underpin cognitive development are of major interest in neuroscience. Of the many aspects of neuroanatomy to consider, tertiary sulci are particularly attractive as they emerge last in gestation, show a protracted development after birth, and are either human- or hominoid-specific. Thus, they are ideal targets for exploring morphological-cognitive relationships with cognitive skills that also show protracted development such as working memory (WM). Yet, the relationship between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 97 publications
6
74
0
Order By: Relevance
“…Specifically, we show that individual differences in IFRMS depth predict individual differences in ADOS score in which the deeper the sulcus, the lower the ADOS score. The fact that only sulcal depth, but not other morphological features, were correlated with ADOS score is consistent with recent results showing a relationship between sulcal depth in lateral prefrontal cortex and higher-level aspects of cognition such as relational reasoning (Voorhies et al, 2021) and working memory (Yao, Voorhies, Miller, Bunge, & Weiner, 2022) in a developmental cohort, as well as inferior frontal cortex in ASD individuals. In terms of the latter, Brun et al (2016) found that sulcal pit depth in the left hemisphere of the ascending ramus of the lateral fissure was correlated with social communication behavior in ASD individuals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, we show that individual differences in IFRMS depth predict individual differences in ADOS score in which the deeper the sulcus, the lower the ADOS score. The fact that only sulcal depth, but not other morphological features, were correlated with ADOS score is consistent with recent results showing a relationship between sulcal depth in lateral prefrontal cortex and higher-level aspects of cognition such as relational reasoning (Voorhies et al, 2021) and working memory (Yao, Voorhies, Miller, Bunge, & Weiner, 2022) in a developmental cohort, as well as inferior frontal cortex in ASD individuals. In terms of the latter, Brun et al (2016) found that sulcal pit depth in the left hemisphere of the ascending ramus of the lateral fissure was correlated with social communication behavior in ASD individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, generally, gyri have negative values, while sulci have positive values. Given the shallowness and variability in the depth of tertiary sulci (Voorhies et al, 2021; Yao, Voorhies, Miller, Bunge, & Weiner, 2022), some mean depth values extend below zero. We emphasize that this just reflects the metric implemented in FreeSurfer.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the patterning and cognitive relevance of the pimfs has only been examined in neurotypical populations [23,24,56]. Numerous studies of disorders such as schizophrenia, autism spectrum disorder, obsessive-compulsive disorder, and fronto-temporal dementia have found that variations in sulcal incidence are clinically relevant -although most of this work has focused on the ACC (e.g., [95][96][97][98][99][100][101][102][103]) and orbitofrontal cortex (for review see [104]).…”
Section: Discussionmentioning
confidence: 99%
“…Although this project focused on a single sulcus, the manual identification of all LPFC sulci (2,877 sulcal definitions across all 72 participants) was required to ensure the most accurate definitions of the pimfs components. For in-depth descriptions of all LPFC sulci, see [23,30,[55][56][57]60]. The incidence rates of the two pimfs components (i.e., sulcal patterning) were compared within and between hemispheres with Chi-squared and Fischer exact tests, respectively.…”
Section: (Ii) Defining the Presence And Prominence Of The Para-interm...mentioning
confidence: 99%
“…For the present study, we re-assessed the 144 human hemispheres analyzed in our prior work 20 . Manual lines were drawn on the FreeSurfer inflated cortical surface to define sulci with tools in tksurfer based on the most recent schematics of sulcal patterning in PMC by Petrides 60 , as well as by the pial and smoothwm surfaces of each individual as in our prior work 20,27,28,36 . In some cases, the precise start or end point of a sulcus can be difficult to determine on a surface 82 .…”
Section: Methodsmentioning
confidence: 99%